9. The Effect Of L-Arginine On Decreasing Foam Cell Development Post Surgical Embolectomy With Fogarty Balloon Catheter On Iliac Arteries Of Rabbit - Firdausy Kurnia Maulana; Romziah Sidik; Ngakan Made Rai Widjaja (Jurnal Medika Veterinaria, 2021)
Vascular injury caused by Fogarty balloon cathetering lead on endothelial dysfunction and trigger the development of foam cell, early atherosclerosis plaque. L-Arginine, as a nitric oxide precursor, has shown to decrease foam cell development. The aim of this study is to prove the effect of L-Arginine on decreasing the amount of foam cell post surgical embolectomy with Fogarty balloon catheter on iliac arteries of rabbit. Sixteen male rabbits were randomized divided into two group of treatment (n=8). After surgical embolectomy in right iliac artery has done, rabbits were fed standard ration (T0) and standard ration with oral L-Arginine (T1). At 28 days after surgical embolectomy, necropsy was done and foam cells were counted. Vascular injury by Fogarty balloon catheter resulted in the development of foam cells both in T0 (13.38 ±14.64) and T1(1.49 ± 1.20). Unpaired t test result showed not significant different (p0.05). The conclusion of this research is L-Arginine reduces the amount of foam cell post surgical embolectomy with Fogarty balloon catheter on iliac arteries of rabbit, however statistical test did not show any difference.